Biological evaluation of 99mTc-ethambutol for early detection of tuberculosis infection in animal model - Rizky Juwita; Sugiharti .; Yana Sumpena; Maula Eka; Sriyani Nanny Kartini (Indonesian Journal of Pharmacy, 2009)
Tuberculosis (TB) is the single most infectious disease, killing millions of people globally. Conventional modalities for TB detection many times the disease is diagnosed at delayed stage and can not use for deep seated infection. Therefore, research and development of 99mTc ethambutol to detect and locate TB at an early stage in any anatomical site have been conducted in PTNBRBATAN Bandung. The result of biological evaluation of 99mTc-ethambutol which studied in rat and mice are as follow, biodistribution study showed accumulation of 99mTc-ethambutol in thigh with infected TB at 4 hours post injection via vein with ratio 2.90 target/non target. Blood clearence studies exhibited 44.96 % of 99mTc-ethambutol remain in the blood within 5 minutes of 99mTc-ethambutol administration. Renal clearance study exhibited of 79.52 % 99mTc-ethambutol excreted from the urine after 24 hours. The images were acquired with a Gamma-camera at different time intervals 1.2 3 and 4 hours showed localization of the 99mTc-ethambutol in infected TB animal model. This study showed that 99mTc-ethambutol is a promises radiopharmaceutical to detect TB infection rapidly and has accuracy with high sensitivity and specificity.Key words : radiopharmaceutical, 99mTc-ethambutol, imaging, Mycobacterium tuberculosis.